The Influence of Financial Knowledge, Financial Attitudes, and Financial Behavior on Investment Decisions of Millennial Generation Workers in Palangka Raya City - Pretti; Solikah Nurwati; Ani Mahrita (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This study aims to determine whether financial knowledge, financial attitudes, and financial behavior influence the investment decisions of millennial generation workers in Palangka Raya City and whether financial knowledge, financial attitudes, and financial behavior have a joint influence on the investment decisions of millennial generation workers in Palangka Raya City.Design/Methodology/Approach – This research method uses a quantitative research method with the SPSS analysis tool. The population of this study was millennial workers in Palangka Raya City with a sample size of 96 respondents using a non-probability sampling technique obtained through a questionnaire.Findings – Research results: 1) Financial knowledge has a positive effect on investment decisions for millennial workers in Palangka Raya City. (2) Financial attitudes have a positive effect on investment decisions for millennial workers in Palangka Raya City. (3) Financial behavior has a positive effect on investment decisions for millennial workers in Palangka Raya City. (4) Financial knowledge, financial attitudes, and financial behavior simultaneously influence investment decisions for millennial workers in Palangka Raya City.Implications – This research can provide awareness for the millennial generation in the city of Palangka Raya to better understand and study financial knowledge, financial attitudes, and financial behavior for investment decisions, in order to obtain maximum profits and minimize the risks of investments made.